AB0471 Optimization of biological treatment in rheumatic diseases. A new way to save?. (23rd January 2014) - Calvet, J.; Gomez, A.; Garcia-Manrique, M.; Galisteo, C.; Moreno, M.; Moron, A.; Graell, E.; Gratacόs, J.; Larrosa, M.
Abstract : Background: The advent ofbiological drugs has been a breakthrough in the treatment of inflammatory rheumatic diseases, but their price is high.There is consensus on when to start treatment and on the follow-up of patients. The latest consensus introduced the concept of increasing time intervals between dose or discontinuingthe biological treatmentin patients in remission but did not defined how. There are some studies, such as Smolen et al, which guide us towards a possible dose reduction in patients who are in remission. Objectives: – To evaluate drug dose reduction without affecting efficacy – To quantify the economic benefit of dosage reduction – To assess differences between diseases treated with biologic drugs Methods: A patients database was used in which biological treatment was registered and updated. An empirical therapeutic dosage reduction, spacing the interval of administration, following the usual controls was made in patients in remission or low disease activity. In the case of flare, dosage was increased to previously effective dose. The annual price of biological treatment was obtained from the Pharmacy Department. The savings from increasing or reducing treatment were calculated and classified by disease. In weight-dependent treatments, 70kg were extrapolated. Results: Two-hundred and twenty-eight patients were on biological treatment during2011. Dose was reduced in59 (25.87%) and increased in 9 patients (3.9%). The number of patients in which the interval between treatment administration was increasedwere: 12adalimumab, 1 anakinra, 24 etanercept, 9 infliximab, 9 rituximab and 4 tocilizumab. For therapeutic increases in dose there were 8 patients on infliximab and 1 on adalimumab.No significant differences indisease activity scores between before and after spacing were observed. The overall cost of biological treatment during 2011 was €2, 623, 320.72. The hypothetical cost in those patients with dose changes would have been €774, 476.67, but actual spending was €625, 862.24; due to dose adjustments, taking into account patients with either reduced or increased dosing.This resulted in a saving of €148, 613.98 (5.6% of total expenditure and 19.2% in patients with dose changes). Differentiating by disease, in patients with dose changes, drug cost reductionwas €111, 977.16 (28.7%) for RA, €27, 847.62 (7.5%) forgroup of spondyloarthropathies (ankylosing spondylitis, psoriatic arthritis, juvenile idiopathic arthritis) and €8789 (93.3%) for Still's disease. See Table 1 . Conclusions: Dose reductionin patients treated with biologic therapy is feasible and favorable pharmacoeconomically. Tight control of these patients by rheumatologists with expertise in managing this type of medication could be of paramount importance in order to optimize these treatments and cut down costs by reducing dose in patients who are in remission. References: Smolen J, et al. L1 ACR Late Breaking Abstract, Novembre 8, 2011, Chicago. Disclosure of Interest: None Declared